Correlation between Density of Vibrio Bacteria with Oscillatoria sp. Abundance on Intensive Litopenaeus vannamei Shrimp Ponds - Heri Ariadi; Mohammad Mahmudi; Mohamad Fadjar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
The abundance of Vibrio bacteria and the presence of an excess Oscillatoria sp plankton type are the main problems that often arise in intensive vanamei (Litopenaeus vannamei) shrimp culture. To examine this problem, the purpose of this study was to determine of model approach interaction between the abundance of Vibrio and Oscillatoria sp with the shrimp growth rate in ponds. This research was conducted with the ex-pose facto design on intensive shrimp culture operations in Bayeman Village, Probolinggo. The results data from field research variable are analyzed using a dynamic modeling system. From the modeling analysis results, showed that the Oscillatoria sp abundance pattern tended to increase over with shrimp culture period as following the pattern of tropical status dynamics by the nutrient increase load of 16.37%/week in ponds ecosystem. Meanwhile, the increase of Vibrio colonies density in ponds continued to increase aggregately by 0.99%/week on nine weeks and 12.5% / week on the last eight weeks of shrimp culture periods. So, it can be concluded that the fluctuations density of vibrio and Oscillatoria sp bacteria in ponds is are bioecological responses from increased nutrient loads and other micromaterials in ponds due to the longer period of shrimp culture.